Factors associated with low physical activity: a cross-sectional study in workers of a Peruvian clinic - Condori, Irene; Soncco-Llulluy, Fernando; Li, Jair; Rosales-Rimache, Jaime (International Journal of Occupational Safety and Health, 2025)
Introduction: Low physical activity in workers is an occupational health problem that significantly increases the risk of developing chronic diseases, such as cardiovascular diseases, type 2 diabetes, hypertension, and obesity. This negatively impacts their physical well-being, productivity, and overall quality of life. Methods: A cross-sectional study was used during the year 2019 to identify the factors associated with low physical activity in 131 health and administrative workers from a Peruvian clinic. Physical activity was evaluated with the instrument "International Physical Activity Questionnaire". Results: The median age was 37.0 years, and 72.5% were women. The median BMI was 25.6 kg/m2, with overweight and obesity prevalences of 51.9% and 11.5%, respectively, and 13.7% presented low physical activity. The physical workload score was lower in workers with high physical activity (8.6, IQR: 6.9-13.0) compared to moderate physical activity (5.9, IQR: 3.6-9.0) and low physical activity (3.8, IQR: 3.0-4.8). The multivariate analysis showed that the physical workload score was the only variable significantly associated with physical activity. Conclusion: Having a higher physical workload significantly decreases low physical activity in clinic workers. It is crucial that physical inactivity prevention programs at work encourage standing or walking meetings, ensure ergonomic sit-stand workstations, and allow breaks to break static posture.